Expectancy Violation Drives Memory Boost for Stressful Events - Kalbe, Felix; Bange, Stina; Lutz, Annika; Schwabe, Lars (Psychological Science, 2020)
Stressful events are often vividly remembered. Although generally adaptive to survival, this emotional-memory enhancement may contribute to stress-related disorders. We tested here whether the enhanced memory for stressful events is due to the expectancy violation evoked by these events. Ninety-four men and women underwent a stressful or control episode. Critically, to manipulate the degree of expectancy violation, we gave participants either detailed or minimal information about the stressor. Although the subjective and hormonal stress responses were comparable in informed and uninformed participants, prior information about the stressor abolished the memory advantage for core features of the stressful event, tested 7 days later. Using functional near-infrared spectroscopy, we further linked the expectancy violation and memory formation under stress to the inferior temporal cortex. These data are the first to show that detailed information about an upcoming stressor and, by implication, a reduced expectancy violation attenuates the memory for stressful events.